Evidence-Based Practice and Policy: Choices Ahead - Gambrill, Eileen (Research on Social Work Practice, 2006)
Choices about how to view evidence-based practice (EBP) are being made by educators, practitioners, agency administrators, and staff in a variety of organizations designed to promote integration of research and practice such as clearinghouses on EBP. Choices range from narrow views of EBP such as use of empirically based guidelines and treatment manuals to the broad philosophy and evolving process of EBP, envisioned by its originators, that addresses evidentiary, ethical, and application issues in a transparent context. Current views of EBP and policy are reviewed, and choices that reflect the adopted vision and related indicators are described. Examples include who will select the questions on which research efforts are focused, what outcomes will be focused on, who will select them and on what basis, how transparent to be regarding the evidentiary status of services, how clients will be involved, and whether to implement needed organizational changes. A key choice is whether to place ethical issues front and center.
Keywords: méthodes de recherche; politique éducative; utilisation des recherches